Case Study of Risk Factors Caused Residual Schizophrenia - Emilia Tiffani; Fitrania Maghfiroh (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
Residual schizophrenia refers to the enduring symptoms of schizophrenia that persist even after acute psychotic episodes have been managed. This study utilizes Freud's psychoanalytic theory to explore how early trauma and authoritarian parenting styles contribute to the development and persistence of residual schizophrenia. Through a case study methodology involving clinical interviews and psychological assessments, this research integrates psychoanalytic insights with schizophrenia research. Findings indicate that early trauma, such as bullying during adolescence, combined with authoritarian parenting, significantly impacts the onset of schizophrenia. Freud’s concepts of the id, ego, and superego provide a framework to understand the psychological conflicts and defense mechanisms involved, emphasizing how repressed memories and a strict upbringing can exacerbate symptoms. The study underscores the importance of psychoanalytic theory in examining the influence of early experiences and family dynamics on schizophrenia, suggesting that addressing these underlying psychological factors is crucial for effective treatment and recovery.